Survey on Object Tracking using Deep Learning Paradigms - Alhuzami, Saad (Transactions on Engineering and Computing Sciences, 2020)
The field of object tracking extends across different domains. It is a major key player in the field of image processing and pattern recognition. Object tracking is the process of tracking an object over a continuous sequence of image frames to determine over time the relative movements or changes. With the massive advancements in the field of deep learning, the use of deep neural networks has risen due to their impressive accomplishments in object detection and tracking. In this Survey, the objective is to give a comprehensive overview of the recent attempts in the field of object tracking with a focus on the use of deep learning techniques and algorithms. The paper is divided into four sections; at first, we will give an overview of the recent work to highlight the techniques and methods which have been used in object tracking using deep learning. The second section focus is on the object tracking that uses convolutional networks techniques. The third section focuses on some of the recurrent neural networks to tack objects. The final section is concentrated on auto-encoders object tracking.